Empowering women entrepreneurs: The impact of integrated medical insurance system in China - Ling Liu; Xu Zong (PLoS ONE, 2026)
China’s urban-rural Integrated Medical Insurance System (IMIS) has expanded universal health coverage, reducing disparities in healthcare access between urban and rural populations and addressing challenges such as unequal access to medical care and reimbursement barriers for disadvantaged groups. Previous research highlights that health insurance influences medical risk, labor mobility, and income distribution, with women valuing and utilizing health insurance more than men. This study investigates IMIS’s impact on women’s entrepreneurship in China using data from the China Family Panel Studies (CFPS) and the China Statistical Yearbook. A Difference-in-Differences (DID) analysis reveals that IMIS increases the likelihood of women’s entrepreneurship by 9.6 percentage points, with robustness confirmed through multiple tests. The study identifies reduced medical expenditure risk, increased access to high-risk occupations, and enhanced household bargaining power as key mechanisms driving this effect. Heterogeneity analyses show that younger women, those with higher education, rural-urban migrants, women with children, those in poorer health, and those with lower household income get greater benefits, underscoring IMIS’s inclusivity. These findings demonstrate that IMIS promotes women’s entrepreneurship, enhancing economic performance and welfare.